PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA KELAS 5 PADA MATA PELAJARAN PKN DI SD MUHAMMADIYAH KAUMAN TAHUN 2016/ 2017 - Septiana, Tri Siwi; Kurniawan, M. Ragil (universitas Ahmad Dahlan, 2018)
This study aims to improve students' critical thinking skills in Civics in 5th grade students of SD Muhammadiyah Kauman, Yogyakarta using Problem Based Learning model. This research is a Classroom Action Research (PTK). The subjects of the study were 5th grade students of B1 SD Muhammadiyah Kauman. The object of research is the whole process and the results of learning Civics with the application of Problem Based Learning model. This research was conducted at SD Muhammadiyah Pakel Yogyakarta in April until May 2017. Data collection techniques used were observation, diary, interview and test. Data analysis technique is done descriptively qualitative. This research was conducted in 2 cycles by applying problem based learning model. The learning steps that were implemented were changes in the delivery of the subject matter, the students analyzed the problem, the formation of the discussion group with the grouping of students based on their achievement, the students in group for discussion, the group members delivered the discussion result in front of the class.The results showed that the critical thinking ability of the 5th grade students of B1 SD Muhammadiyah Kauman, Yogyakarta increased after the use of Problem Based Learning model in Civics learning with the subject matter of the example of central and regional legislation. This improvement is evident in the improvement of students' critical thinking skill test result from 12.90% pretreatment score to 51.61% (enough) in cycle I and increased to 70.96% (good) in cycle II. The results of activity observations related to students' critical thinking skills are increased among others: active students in learning, students more freely in finding and collecting desired information, and students also have more opportunities to learn with friends.